The Influence of Market Structure in Indonesian Banking Performance - Naylah, Maal; Cahyaningratri, Cahyaningratri (Universitas Negeri Semarang, 2020)
There are three hypotheses about structure-conduct-performance paradigm; traditional hypothesis, differentiation hypothesis and efficiency hypothesis. The objective of this research is to examine how strong the influence of market structure in banking performance. This study uses the fix effect model by applying the Weiss model. This research also tries to prove whether market share and concentration in the banking industry as a proxy to efficiency. The result of the panel data analysis conducted on a sample of 15 biggest commercial banks over the period from 2009 to 2018 is strongly reject the traditional hypothesis. The empirical findings suggest that market concentration has a negative correlation between profitability, it means that Indonesian banking industry strongly reject the traditional hypothesis and support efficiency hypothesis and there is a positive correlation between market share and profitability, supports the differentiation hypothesis.